Electrode-integrated separator for lithium ion secondary battery and lithium ion secondary battery including same
By forming an adhesive part pattern on the electrode active material layer of the lithium-ion secondary battery and using a porous layer, the problem of insufficient thermal stability and adhesion of the separator is solved, and excellent adhesion of the lithium-ion secondary battery is achieved at high temperatures Combining durability and ionic conductivity avoids internal short circuits and improves battery stability and safety.
Patent Information
- Application Number
- CN202380033838.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-26
- Filing Date
- 2023-10-13
- Publication Date
- 2024-12-20
AI Technical Summary
The separators of the existing lithium-ion secondary batteries have poor thermal stability and insufficient adhesion at high temperatures, which can easily lead to the interface between the electrode and the separator to be disengaged or wrinkled, and the insulating characteristics of the inorganic coating separator are low, which can easily cause the internal Short circuit.
The bonding part pattern is formed on the electrode active material layer and is closely bonded to the electrode active material layer through a porous layer. The porous layer contains a polymer binder and inorganic fine particles dispersed in the polymer, thereby enhancing the electrode and the separator. adhesion durability and ionic conductivity.
Excellent bonding durability between the electrode and the separator and the ionic conductivity of the electrode are achieved at high temperatures, avoiding internal short circuits and capacity reduction, and improving the stability and safety of the lithium-ion secondary battery.
Smart Images

Figure CN119174046A_ABST
Abstract
Description
Technical Field
[0001] CROSS-REFERENCE TO RELATED APPLICATIONS
[0002] This application claims the benefit of Korean Patent Application No. 10-2022-0141272 filed in the Korean Intellectual Property Office on October 28, 2022, and Korean Patent Application No. 10-2023-0129785 filed in the Korean Intellectual Property Office on September 26, 2023, the disclosures of which are incorporated herein by reference in their entirety.
[0003] The present invention relates to an electrode-integrated separator for a lithium-ion secondary battery and a lithium-ion secondary battery including the same. Background Art
[0004] As mobile phones, laptops, tablet computers, mobile batteries, electric vehicles, personal mobile devices, etc. become highly functionalized, the demand for secondary batteries used as their driving power sources is steadily increasing. In particular, lithium secondary batteries with high operating voltage and high energy density / unit weight are most frequently used.
[0005] The lithium-ion secondary battery is configured so that an electrode assembly having a positive electrode / separator / negative electrode structure that can be charged and discharged is installed in a battery box. The positive electrode and the negative electrode are manufactured by applying a slurry containing an electrode active material to one or both surfaces of a metal current collector, followed by drying and rolling.
[0006] The separator is one of the most important factors that determine the life of the secondary battery and electrically isolates the positive electrode from the negative electrode. In addition, the separator is required to have ion permeability and mechanical strength so that the electrolyte solution can pass through the separator smoothly. With the expansion of the application of high-energy lithium secondary batteries, the safety of the separator at high temperatures is also increasingly required.
[0007] The problem of the conventionally used separator including a separator substrate and an inorganic coating is that due to its material properties, the adhesion between the separator and the electrode is insufficient, thereby causing a problem of partial detachment or wrinkling at the interface between the electrode and the separator. Polyolefins commonly used as separator substrates have a thermal stability problem in which the polyolefin melts at high temperatures.
[0008] In order to solve these problems, a method of eliminating the polyolefin separator substrate and using only an inorganic coating film to construct the separator has been proposed. However, such a separator still does not have sufficient adhesion to the electrode and has extremely low insulation properties, so it is easy to short-circuit internally when applied to an electrochemical device. In addition, such a separator has a fatal disadvantage: the separator is easily torn due to its low tensile strength and elongation, and a micro short circuit occurs inside the electrode assembly. Summary of the invention
[0009] Technical issues
[0010] An object of the present invention is to provide an electrode-integrated separator for a lithium ion secondary battery having excellent adhesion durability between the separator and electrodes without impairing ion conductivity between the electrodes.
[0011] Another object of the present invention is to provide a lithium ion secondary battery including the electrode-integrated separator.
[0012] Technical Solution
[0013] According to one embodiment of the present invention, there is provided an electrode-integrated separator for a lithium-ion secondary battery, comprising:
[0014] an electrode portion, the electrode portion comprising an electrode active material layer stacked on an electrode current collector;
[0015] forming a bonding portion pattern on the electrode active material layer; and
[0016] A porous layer is closely bonded to the electrode active material layer through a bonding portion pattern and contains a polymer binder and inorganic fine particles dispersed in the polymer binder.
[0017] According to another embodiment of the present invention, there is provided a lithium ion secondary battery including the above-mentioned electrode-integrated separator.
[0018] Now, an electrode-integrated separator for a lithium ion secondary battery and a lithium ion secondary battery including the same according to an embodiment of the present invention will be described in more detail.
[0019] The terms or words used in this specification and claims should not be construed as limited to common terms or dictionary terms, and the present invention should be interpreted with meanings and concepts consistent with the technical ideas of the present disclosure based on the principle that the inventors can appropriately define the concepts of the terms to appropriately describe their own invention in the best manner.
[0020] Unless otherwise defined, all technical terms and scientific terms used herein have the same meaning as commonly understood by those of ordinary skill in the art to which the invention belongs. The terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of the invention.
[0021] As used herein, the singular forms “a”, “an” and “the” are intended to include the plural forms as well, unless the context clearly indicates otherwise.
[0022] It should be understood that the terms "including", "comprising", "having" and the like are used herein to specify the presence of stated features, regions, integers, steps, actions, elements and / or components, but do not exclude the presence or addition of other features, regions, integers, steps, actions, elements, components and / or groups.
[0023] Although the present invention can be modified in various ways and take various alternative forms, its specific embodiment will be described and described in detail below. However, it should be understood that it is not intended to limit the present invention to the specific form disclosed, but on the contrary, the present invention covers all modifications, equivalents and alternatives that fall within the spirit and scope of the present invention.
[0024] When describing a positional relationship, for example, when the positional relationship is described as “on,” “over,” “below,” and “close to,” unless “just” or “directly” is used, one or more other parts may be arranged between the two parts.
[0025] When describing a time relationship, for example, when a time sequence is described as “after,” “subsequently,” “next,” and “before,” discontinuous cases may be included unless “just” or “directly” is used.
[0026] As used herein, the term “at least one” should be understood to include any and all combinations of one or more of the associated listed items.
[0027] In the present invention, any one layer being bonded to another layer "through" another layer means that one layer and another layer are stacked and bonded with another layer interposed in at least a partial region between the one layer and the another layer.
[0028] In the present invention, any one layer being "closely bonded" to another layer through another layer means that the layers are stacked and bonded through another layer without any empty space between the one layer and the another layer.
[0029] According to one embodiment of the present invention, there is provided an electrode-integrated separator for a lithium-ion secondary battery, comprising:
[0030] an electrode portion, the electrode portion comprising an electrode active material layer stacked on an electrode current collector;
[0031] forming a bonding portion pattern on the electrode active material layer; and
[0032] A porous layer is closely bonded to the electrode active material layer through a bonding portion pattern and contains a polymer binder and inorganic fine particles dispersed in the polymer binder.
[0033] As a result of intensive studies, the present inventors have found that a lithium ion secondary battery satisfying the above configuration can exhibit excellent adhesion durability between a separator and electrodes without impairing ion conductivity between electrodes.
[0034] Figure 1 is a cross-sectional view of an electrode-integrated separator for a lithium secondary battery according to one embodiment of the present invention.
[0035] Reference Figure 1 , an electrode integrated separator 100 for a lithium secondary battery according to one embodiment of the present invention includes: an electrode portion 10, the electrode portion 10 including an electrode active material layer 15 stacked on an electrode current collector 13; a bonding portion pattern 20 formed on the electrode active material layer 15; and a porous layer 30, the porous layer 30 being tightly bonded to the electrode active material layer 15 through the bonding portion pattern 20.
[0036] In particular, the electrode integrated separator 100 for a lithium ion secondary battery has a structure in which the porous layer 30 is closely bonded to the electrode active material layer 15 of the electrode unit 10 through the bonding portion pattern 20. Therefore, the electrode integrated separator 100 can exhibit excellent bonding durability between the porous layer 30 and the electrode unit 10 while exhibiting excellent thermal stability and ion conductivity between electrodes.
[0037] According to one embodiment of the present invention, the electrode portion 10 may be a negative electrode portion and a positive electrode portion.
[0038] The electrode part 10 may be obtained by applying an electrode material including a mixture of an electrode active material, a conductive material, and a binder onto an electrode current collector 13 and then drying the electrode material to form an electrode active material layer 15 .
[0039] As the electrode current collector, those known in the art to which the present invention belongs that have conductivity and do not cause chemical changes in lithium ion secondary batteries can be used. In one example, the electrode current collector may include stainless steel; aluminum; nickel; titanium; fired carbon; or aluminum or stainless steel with a surface treated with carbon, nickel, titanium, silver, etc.
[0040] Preferably, the thickness of the electrode current collector may generally be 3 μm to 500 μm. The electrode current collector may have fine protrusions and depressions formed on its surface to enhance adhesion to the electrode active material. The electrode current collector may be used in various forms, such as films, sheets, foils, nets, porous bodies, foams, and nonwoven fabric structures.
[0041] Conductive materials can be used to impart electronic conductivity to the electrodes.
[0042] The conductive material can be used without particular limitation, as long as it has electronic conductivity without causing chemical changes in the lithium ion secondary battery. As a non-limiting example, the conductive material may include carbon-based materials such as carbon black, acetylene black, ketjen black, channel black, furnace black, lamp black, thermal black, and carbon fiber; graphite such as natural graphite and artificial graphite; metal powder or metal fiber such as copper, nickel, aluminum, and silver; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; or conductive polymers such as polyphenylene derivatives. As the conductive material, only any one of the above examples may be used or a mixture of two or more of the above examples may be used.
[0043] The content of the conductive material can be adjusted within a range that does not cause a decrease in battery capacity while exhibiting an appropriate level of conductivity. Preferably, the content of the conductive material can be 1 wt % to 10 wt %, or 1 wt % to 5 wt %, based on the total weight of the electrode material.
[0044] Binders are used to properly attach the electrode material to the electrode current collector.
[0045] As a non-limiting example, the binder may include polyvinyl alcohol, polyacrylate, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon resin, etc. As the binder, one of the above examples or a mixture of two or more thereof may be used.
[0046] The content of the binder can be adjusted within a range that exhibits an appropriate level of adhesive properties without causing a decrease in battery capacity. Preferably, the content of the binder can be 1 wt % to 10 wt %, or 1 wt % to 5 wt %, based on the total weight of the electrode material.
[0047] When the electrode portion 10 is a positive electrode portion, a positive electrode active material may be used without particular limitation as long as it is a material capable of reversibly intercalating / deintercalating lithium ions.
[0048] In one example, the positive electrode active material may be a composite oxide or phosphate containing cobalt, manganese, nickel, iron, or a combination of these metals and lithium.
[0049] In another example, the positive electrode active material may be a compound represented by any one of the following chemical formulas: Li a A 1-b R b D2(0.90≤a≤1.8, 0≤b≤0.5); Li aHAVE BEEN 1-b R b O 2-c D c (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05);LiE 2-b R b O 4-c D c (0≤b≤0.5,0≤c≤0.05);Li a Ni 1-b-c Co b R c D d (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0 <d≤2);Li a Ni 1-b-c Co b R c O 2-d Z d (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0 <d<2);Li a Ni 1-b-c Co b R c O 2-d Z2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0 <d<2);Li a Ni 1-b- c Mr b R c D d (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0 <d≤2);Li a Ni 1-b-c Mr b R c O 2-d Z d (0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0 <d<2);Li a Ni 1-b-c Mr b R c O 2-d Z2(0.90≤a≤1.8,0≤b≤0.5,0≤c≤0.05,0 <d<2);Li a Ni b HAVE BEEN c G d O2(0.90≤a≤1.8,0≤b≤0.9,0≤c≤0.5,0.001≤d≤0.1);Li a Ni b Coc Mn d G e O2 (0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0.001≤e≤0.1); Li a NeG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a CoG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a MnG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn b O4(0.90≤a≤1.8, 0.001≤b≤0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiTO2; LiNiVO4; Li (3-f) J2(PO4)3(0≤f≤2);Li (3-f) Fe2(PO4)3(0≤f≤2); and LiFePO4.
[0050] In the above chemical formula, A is Ni, Co, Mn or a combination thereof; R is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element or a combination thereof; D is O, F, S, P or a combination thereof; E is Co, Mn or a combination thereof; Z is F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; Q is Ti, Mo, Mn or a combination thereof; T is Cr, V, Fe, Sc, Y or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu or a combination thereof.
[0051] Those having a coating on the surface of the positive electrode active material can be used, or a mixture of the positive electrode active material and the positive electrode active material having a coating can be used. As the coating element contained in the coating, Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr or a mixture thereof can be used.
[0052] According to one embodiment, the positive electrode active material may be included in an amount of 80 wt % to 95 wt % based on the total weight of the electrode material. Preferably, the content of the positive electrode active material may be 82 wt % to 95 wt %, or 82 wt % to 93 wt %, or 85 wt % to 93 wt %, or 85 wt % to 90 wt %, based on the total weight of the electrode material.
[0053] When the electrode part 10 is a negative electrode part, the negative electrode active material may include a material capable of reversibly inserting and extracting lithium ions, lithium metal, a lithium metal alloy, a material capable of doping and dedoping lithium, and a transition metal oxide.
[0054] As the material capable of reversibly inserting and extracting lithium ions, crystalline carbon, amorphous carbon or a mixture thereof as a carbonaceous material can be exemplified. Specifically, the carbonaceous material can be natural graphite, artificial graphite, kish graphite, pyrolytic carbon, mesophase pitch, carbon fiber based on mesophase pitch, mesocarbon microbeads, coke derived from petroleum or coal tar pitch, soft carbon, hard carbon, etc.
[0055] The lithium metal alloy may include an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, Sn, Bi, Ga and Cd.
[0056] The material capable of doping and dedoping lithium may include Si, Si-C composite material, SiO x (0 < x < 2), Si-Q alloy (where Q is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements and combinations thereof, but not Si), Sn, SnO2, Sn-R (where R is an element selected from alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, Group 15 elements, Group 16 elements, transition metals, rare earth elements and combinations thereof, but not Sn), etc. In addition, as the material capable of doping and dedoping lithium, at least one of the above examples may be mixed with SiO2 and then used. Q and R may be Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, etc.
[0057] In addition, the transition metal oxide may include vanadium oxide, lithium vanadium oxide, lithium titanium oxide, etc.
[0058] Preferably, the negative electrode active material may include one or more compounds selected from carbonaceous materials and silicon compounds. Herein, the carbonaceous material is a material containing at least one selected from the following: natural graphite, artificial graphite, condensable graphite, pyrolytic carbon, mesophase pitch, mesophase pitch-based carbon fiber, mesophase carbon microbead, coke derived from petroleum or coal tar pitch, soft carbon, and hard carbon, as exemplified previously. In addition, the silicon compound may be a Si-containing compound exemplified previously, i.e., Si, Si-C composite, SiOx (where 0 < x < 2), Si-Q alloy, a mixture thereof, or a mixture of at least one of them and SiO2.
[0059] According to one embodiment, based on the total weight of the electrode material, the negative electrode active material may be included in an amount of 85 wt% to 98 wt%. Preferably, based on the total weight of the negative electrode material, the content of the negative electrode active material may be 85 wt% to 97 wt%, or 87 wt% to 97 wt%, or 87 wt% to 95 wt%, or 90 wt% to 95 wt%.
[0060] Meanwhile, the electrode integrated separator 100 for a lithium ion secondary battery includes an adhesive portion pattern 20 formed on the electrode active material layer 15 of the electrode portion 10.
[0061] The adhesive portion pattern 20 is a pattern in which a plurality of adhesive portion units are arranged at a predetermined interval. The adhesive portion pattern 20 is formed on the electrode active material layer 15 to improve the adhesive durability between the porous layer 30 and the electrode portion 10.
[0062] According to one embodiment, the adhesive portion pattern 20 may have a form including two or more or four or more adhesive portion units.
[0063] In order to achieve the effect of improving the adhesive durability between the porous layer 30 and the electrode portion 10 by introducing the adhesive portion pattern 20, the adhesive portion pattern 20 preferably includes two or more or four or more adhesive portion units. The upper limit of the number of adhesive portion units included in the adhesive portion pattern is not particularly limited because it can be appropriately adjusted according to the ratio of the area of the electrode portion to the area occupied by the adhesive portion pattern.
[0064] According to one embodiment, each of the adhesive portion units may independently have one or more cross-sectional shapes selected from a circle, an ellipse, a sector, a polygon, and a concave polygon.
[0065] Figures 2 to 6 Respectively are cross-sectional views of the adhesive portion pattern according to an embodiment of the present invention.
[0066] Figure 2 The adhesive portion pattern 20 shown in is composed of adhesive portion units 23 having a circular cross-section. Figure 3 The bonding portion pattern 20 shown in FIG. 1 is composed of bonding portion units 23 having a square cross section. Figure 4 The bonding section pattern 20 shown in FIG. 1 is a pattern in which bonding section units 23 having a rectangular cross section are arranged in a stripe shape. Figure 5 The bonding portion pattern 20 shown in FIG. 1 is composed of a bonding portion unit 23 having a circular cross section and a bonding portion unit 25 having a cross-shaped cross section. Figure 6 The bonding portion pattern 20 shown in FIG. 1 is composed of a bonding portion unit 23 having a quarter-circular cross section, a bonding portion unit 25 having a circular cross section, and a bonding portion unit 27 having a semicircular cross section. Figures 2 to 6 A portion of a bonding portion pattern is shown, wherein the bonding portion pattern may be expanded according to the area of the electrode active material, and the number of bonding portion units may be increased.
[0067] According to one embodiment, in order to express uniform bonding durability by introducing the bonding portion pattern, the bonding portion pattern 20 is preferably a pattern in which the central portions of the respective bonding portion units are arranged at equal intervals.
[0068] Here, the center portion of the bonding unit can be determined based on its cross section. In one example, the center portion of a circular cross section is the center of a circle. In another example, the center portion of an elliptical cross section is the point where the major axis and the minor axis of an ellipse intersect. In another example, a fan-shaped cross section such as a quarter circle or a semicircle can be the center of a circle inscribed in a cross section. In another example, the center portion of a cross section that is a polygon or a concave polygon can be the center of a circle circumscribed with a cross section.
[0069] According to one embodiment, the bonding portion pattern 20 may include bonding portion units having two or more cross-sectional shapes selected from a circle, an ellipse, a sector, a polygon, and a concave polygon.
[0070] Here, the bonding portion units having the same cross-sectional shape as each other may be configured such that their central portions are arranged at equal intervals. Figure 5 In the embodiment, the bonding portion units 23 having a circular cross section are arranged at equal intervals based on the center portion thereof. Furthermore, independently, the bonding portion units 25 having a cross-shaped cross section are arranged at equal intervals based on the center portion thereof.
[0071] According to one embodiment, the bonding section units in the bonding section pattern 20 are arranged at intervals such that the distance between the center portions of the respective bonding section units is 100 μm to 1500 μm.
[0072] Specifically, the arrangement distance of the bonding unit is 100 μm or more, or 250 μm or more, or 500 μm or more; and 1500 μm or less, or 1200 μm or less, or 1000 μm or less based on the distance between the center portions of each bonding unit.
[0073] Preferably, the bonding section units may be arranged at intervals such that a distance between center portions of the bonding section units is 100 μm to 1500 μm, or 250 μm to 1500 μm, or 250 μm to 1200 μm, or 500 μm to 1200 μm, or 500 μm to 1000 μm.
[0074] According to one embodiment, a cross section of the bonding section unit may have a major axis diameter of 20 μm to 5000 μm.
[0075] Here, the major axis diameter can be determined as follows based on the cross-sectional shape of the bonding portion unit. In one example, the major axis diameter of a circular cross section means the diameter of a circle. In another example, the major axis diameter of an elliptical cross section means the major axis length of an ellipse. In another example, the major axis diameter of a fan-shaped cross section such as a quarter circle or a semicircle means the length of the line segment connecting the two points where two radii intersect with the arc. Or, it can mean the radius of a quarter circle or the diameter of a semicircle. In yet another example, the major axis diameter of a cross section that is a polygon or a concave polygon means the diameter of a circle circumscribed with a cross section.
[0076] Specifically, the major axis diameter of the cross section of the bonding portion unit may be 20 μm or more, or 100 μm or more, or 200 μm or more; and 5000 μm or less, or 4000 μm or less, or 3000 μm or less.
[0077] Preferably, the major axis diameter of the cross section of the bonding part unit may be 20 μm to 5000 μm, or 100 μm to 5000 μm, or 100 μm to 4000 μm, or 200 μm to 4000 μm, or 200 μm to 3000 μm.
[0078] According to one embodiment, in the bonding section pattern 20, the distance between the center portions of the bonding section units and the major axis diameter of the cross section may be determined within the above range according to the ratio of the area occupied by the bonding section pattern.
[0079] According to one embodiment, the bonding part pattern 20 is preferably formed at an area ratio of 15% to 50% based on the total area of the electrode active material layer 15 .
[0080] Specifically, the ratio of the area occupied by the bonding portion pattern 20 based on the total area of the electrode active material layer 15 is 15% or more, or 16% or more, or 17% or more; and 50% or less, or 49% or less, or 48% or less.
[0081] In order to exhibit the effect of improving the bonding durability between the porous layer 30 and the electrode part 10 by introducing the bonding part pattern 20, the ratio of the area occupied by the bonding part pattern 20 based on the total area of the electrode active material layer is preferably 15% or more, 16% or more, or 17% or more.
[0082] As the ratio of the area occupied by the bonding portion pattern 20 is higher, more excellent bonding durability can be exhibited, but the ion conductivity between the electrodes may decrease, which may lead to a decrease in the capacity of the lithium ion secondary battery. Therefore, based on the total area of the electrode active material layer, the ratio of the area occupied by the bonding portion pattern is preferably 50% or less, or 49% or less, or 48% or less.
[0083] Preferably, the bonding part pattern 20 may be formed at an area ratio of 15% to 50%, 16% to 50%, 16% to 49%, 17% to 49%, or 17% to 48% based on the total area of the electrode active material layer 15 .
[0084] As an example, see Figure 7 and Figure 8 , the area ratio of the bonding portion pattern 20 can be calculated as a unit area (A U ) is the area occupied by the bonding pattern (A P ) percentage.
[0085] According to one embodiment, the material of the bonding part pattern preferably has bonding properties suitable for bonding the electrode active material layer 15 and the porous layer 30 while being electrochemically stable.
[0086] In one example, a binder used to form the positive electrode active material layer and the negative electrode active material layer may be used as the binding part.
[0087] Preferably, the adhesive part can be one or more selected from the following: polyvinyl alcohol, polyacrylate, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin and nylon resin.
[0088] In addition, the polymer binder for forming the porous layer can be applied to the bonding portion. For example, the bonding portion pattern can include one or more selected from the following: polyvinylidene fluoride, poly (vinylidene fluoride-hexafluoropropylene), poly (vinylidene fluoride-trichloroethylene), poly (vinylidene fluoride-chlorotrifluoroethylene), polymethyl methacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, ethylene vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethylated polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, ethylene-propylene-diene terpolymer, sulfonated ethylene-propylene-diene terpolymer, styrene-butadiene rubber, fluororubber and polyimide.
[0089] According to one embodiment, the thickness of the bonding part pattern 20 is preferably adjusted within the range of 0.1 μm to 10 μm, or 0.1 μm to 5 μm, or 0.5 μm to 5 μm, or 0.5 μm to 2 μm to exhibit suitable properties.
[0090] The method of forming the bonding part pattern 20 on the electrode active material layer 15 may be performed by methods such as coating, dispensing, transfer, deposition, printing or spraying. In one example, the bonding part pattern 20 may be formed using methods such as gravure printing, micro gravure printing and offset printing.
[0091] Meanwhile, the electrode-integrated separator 100 for a lithium-ion secondary battery includes the porous layer 30 closely bonded to the electrode active material layer 15 through the bonding part pattern 20 .
[0092] Reference Figure 1 , the porous layer 30 is stacked and bonded via the bonding portion pattern 20 without an empty space between the porous layer 30 and the electrode active material layer 15. Therefore, the electrode integrated separator 100 can exhibit excellent bonding durability between the porous layer 30 and the electrode portion 10 without impairing ionic conductivity between the counter electrode (not shown) stacked on the porous layer 30 and the electrode portion 10.
[0093] According to one embodiment, the porous layer 30 includes a polymer binder and inorganic fine particles dispersed in the polymer binder.
[0094] When swollen with a liquid electrolyte, the polymer binder gels and can therefore show a high degree of swelling. The electrolyte injected after the lithium ion secondary battery is assembled penetrates into the polymer binder, and the polymer binder containing the electrolyte penetrated therein also has electrolyte ion conductivity. Therefore, it is preferred to use a solubility index of 15 MPa 1 / 2 Up to 45MPa 1 / 2 The polymer is used as a polymer binder.
[0095] In one example, the polymer binder can be one or more compounds selected from the following: polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-trichloroethylene), poly(vinylidene fluoride-chlorotrifluoroethylene), polymethyl methacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, ethylene vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethylated polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, ethylene-propylene-diene terpolymer, sulfonated ethylene-propylene-diene terpolymer, styrene-butadiene rubber, fluororubber and polyimide.
[0096] The inorganic fine particles form micropores through empty spaces between the particles, maintain their physical form at high temperatures, and are electrochemically stable.
[0097] The inorganic fine particles are preferably within the operating voltage range of the secondary battery (e.g., based on Li / Li + The inorganic fine particles preferably have a high electrolyte ion transport capacity. The inorganic fine particles preferably have a density as low as possible so that they can be well dispersed in the polymer binder. In addition, the inorganic fine particles preferably have a high dielectric constant to help increase the degree of dissociation of the electrolyte salt in the electrolyte.
[0098] Preferably, the inorganic fine particles may be one or more selected from the group consisting of inorganic particles having a dielectric constant of 1 or more, inorganic particles having piezoelectricity, and inorganic particles having a lithium ion transporting capability.
[0099] In one example, inorganic particles such as SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, boehmite (AlO(OH)), Al(OH)3, TiO2 and SiC have a dielectric constant of 1 or greater and can therefore be suitable for application as inorganic fine particles.
[0100] In another example, inorganic particles with piezoelectricity are non-conductive under normal pressure but exhibit conductivity when a certain pressure is applied due to changes in their internal structure. The piezoelectric inorganic particles have a high dielectric constant characteristic, with a dielectric constant of 100 or greater. In addition, when the piezoelectric inorganic particles are stretched or compressed under a certain range of applied pressure, they become positively (+) charged on one surface and negatively (-) charged on the other surface, thereby generating a potential difference between their two surfaces. Due to the above characteristics of the piezoelectric inorganic particles, when an internal short circuit occurs in the electrodes of a secondary battery due to an external shock, direct contact between the positive and negative electrodes can be prevented, and the voltage can be gradually reduced and the safety can be improved. As the piezoelectric inorganic particles, inorganic particles such as BaTiO3, Pb(Zr,Ti)O3 (PZT), Pb 1- x La x Zr 1-y Ti y O3 (PLZT), Pb(Mg 1 / 3 Nb 2 / 3 )O3 - PbTiO3 (PMN - PT) and HfO2 can be preferably applied.
[0101] In yet another example, inorganic particles with lithium ion transport ability refer to inorganic particles that contain lithium elements but have the function of moving lithium ions without storing lithium. Inorganic particles with lithium ion transport ability can improve the lithium ion conductivity in the battery. Examples of such inorganic particles include inorganic particles such as Li3PO4, Li x Ti y (PO4)3 (0 < x < 2, 0 < y < 3), Li x Al y Ti z (PO4)3 (0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y (0 < x < 4, 0 < y < 13), Li x La y TiO3 (0 < x < 2, 0 < y < 3), Li x Ge y P z S w (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), Li x N y (0 < x < 4, 0 < y < 2), Li x Si y S z (0 < x < 3, 0 < y < 2, 0 < z < 4) and Li x P y Sz (0 < x < 3, 0 < y < 3, 0 < z < 7).
[0102] Preferably, the inorganic fine particles may be one or more selected from the following: SrTiO3, SnO2, CeO2, MgO, NiO, CaO, ZnO, ZrO2, Y2O3, Al2O3, boehmite (AlO(OH)), Al(OH)3, TiO2, SiC, BaTiO3, Pb(Zr,Ti)O3, Pb 1-x La x Zr 1-y Ti y O3, Pb(Mg 1 / 3 Nb 2 / 3 )O3 - PbTiO3, HfO2, Li3PO4, Li x Ti y (PO4)3 (0 < x < 2, 0 < y < 3), Li x Al y Ti z (PO4)3 (0 < x < 2, 0 < y < 1, 0 < z < 3), (LiAlTiP) x O y (0 < x < 4, 0 < y < 13), Li x La y TiO3 (0 < x < 2, 0 < y < 3), Li x Ge y P z S w (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5), Li x N y (0 < x < 4, 0 < y < 2), Li x Si y S z (0 < x < 3, 0 < y < 2, 0 < z < 4) and Li x P y S z (0 < x < 3, 0 < y < 3, 0 < z < 7).
[0103] The particle size of the inorganic fine particles is preferably from 0.001 μm to 10 μm. To ensure dispersibility in the porous layer, the particle size of the inorganic fine particles is preferably 0.001 μm or more. However, if the particle size of the inorganic fine particles is too large, the thickness of the porous layer increases and the mechanical properties deteriorate, and the excessive pore size may cause an internal short circuit during charging and discharging of the secondary battery. Therefore, the particle size of the inorganic fine particles is preferably 10 μm or less.
[0104] According to one embodiment, the porous layer 30 may include 10% to 99% by weight of inorganic fine particles and 1% to 90% by weight of a polymer binder. In order to give the porous layer appropriate porosity and insulating properties, the inorganic fine particles are preferably included in an amount of 10% by weight or more. However, if the inorganic fine particles are included in an excessive amount, the mechanical properties of the porous layer may be reduced due to the weakening of the adhesive force. Therefore, the inorganic fine particles are preferably included in an amount of 99% by weight or less.
[0105] According to one embodiment, the porous layer 30 preferably has a porosity within a range suitable for exhibiting the characteristics of the porous layer. If the porosity of the porous layer is too large, an internal short circuit may occur during charging and discharging of the lithium ion secondary battery. Therefore, the porosity of the porous layer 30 is preferably 60% or less.
[0106] According to one embodiment, the thickness of the porous layer 30 is preferably adjusted within a range of 5 μm to 100 μm, or 5 μm to 50 μm, or 10 μm to 50 μm to exhibit suitable properties.
[0107] According to one embodiment, the method of closely bonding the electrode active material layer 15 to the porous layer 30 through the bonding portion pattern 20 can be performed using a conventional stacking method. In one example, it can be performed by forming the bonding portion pattern 20 on the electrode active material layer 15 of the negative electrode portion 10 and then stacking the porous layer 30 thereon under pressure.
[0108] According to one embodiment of the present invention, a lithium ion secondary battery including the electrode-integrated separator 100 described above is provided.
[0109] In one example, a lithium ion secondary battery may include: an electrode assembly including a counter electrode disposed on a porous layer of an electrode-integrated separator; an electrolyte swelled in the electrode assembly; and a battery case sealing and storing the electrode assembly and the electrolyte.
[0110] Since the lithium ion secondary battery includes the above-described electrode assembly, it may exhibit excellent durability and stable performance.
[0111] The lithium ion secondary battery may have various shapes, such as a prismatic shape, a cylindrical shape, or a pouch shape.
[0112] Lithium ion secondary batteries can be used as energy sources with improved performance and safety in the fields of portable electronic devices such as mobile phones, notebook computers, tablet computers, mobile batteries, and digital cameras, and in the fields of transportation tools such as electric vehicles, electric motorcycles, and personal mobility devices.
[0113] According to one embodiment, the electrolyte can be used without particular limitation, as long as it is known to be suitable for lithium ion secondary batteries in the technical field to which the present invention belongs. For example, the electrolyte can be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc.
[0114] Specifically, the electrolyte may include a non-aqueous organic solvent and a lithium salt.
[0115] The nonaqueous organic solvent may be used without particular limitation as long as it can function as a medium through which ions involved in an electrochemical reaction of a battery can move.
[0116] Specifically, the non-aqueous organic solvents include: ester-based solvents, such as methyl acetate, ethyl acetate, γ-butyrolactone and ε-caprolactone; ether-based solvents, such as dibutyl ether and tetrahydrofuran; ketone-based solvents, such as cyclohexanone; aromatic hydrocarbon-based solvents, such as benzene and fluorobenzene; carbonate-based solvents, such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC) and propylene carbonate (PC); alcohol-based solvents, such as ethanol and isopropanol; nitriles, such as R-CN (wherein R is a C2 to C20 linear, branched or cyclic hydrocarbon group, which may contain a double bond aromatic ring or an ether bond); amides, such as dimethylformamide; dioxolanes, such as 1,3-dioxolane; cyclopentane sulfone, etc.
[0117] In the above examples, a carbonate-based solvent may be preferably used as the non-aqueous organic solvent.
[0118] In particular, considering the charging and discharging performance of the battery and the compatibility with the sacrificial positive electrode material, the non-aqueous organic solvent may preferably be a mixture of cyclic carbonates (e.g., ethylene carbonate and propylene carbonate) having high ionic conductivity and high dielectric constant and linear carbonates (e.g., ethyl methyl carbonate, dimethyl carbonate and diethyl carbonate) having low viscosity carbonates. In this case, mixing and using cyclic carbonates and linear carbonates in a volume ratio of 1:1 to 1:9 may be beneficial to achieving the above-mentioned properties.
[0119] In addition, as the non-aqueous organic solvent, a solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) are mixed in a volume ratio of 1:2 to 1:10; or a solvent in which ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) are mixed in a volume ratio of 1 to 3:1 to 9:1 can be preferably used.
[0120] The lithium salt contained in the electrolyte is dissolved in the non-aqueous organic solvent and serves as a lithium ion source in the battery, which enables the basic operation of the lithium ion secondary battery and facilitates the movement of lithium ions between the positive electrode and the negative electrode.
[0121] The lithium salt may include LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiFSI, LiTFSI, LiCl, LiI and LiB(C2O4)2, etc. Specifically, the lithium salt may be LiPF6, LiFSI, LiTFSI and mixtures thereof.
[0122] The lithium salt may be included in the electrolyte at a concentration of 0.1 M to 2.0 M. Including the lithium salt in the concentration range imparts suitable conductivity and viscosity to the electrolyte, thereby exhibiting excellent electrolyte performance.
[0123] Optionally, the electrolyte may contain additives for the purpose of improving battery life characteristics, suppressing capacity reduction of the battery, improving battery discharge capacity, and the like.
[0124] For example, the additive may include compounds based on halogenated alkylene carbonates, such as difluoroethylene carbonate; or pyridine, triethyl phosphite, triethanolamine, cyclic ethers, ethylenediamine, n-glyme, hexaphosphoric acid triamide, nitrobenzene derivatives, sulfur, quinone imine dyes, N-substituted Oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum trichloride, etc. The additive may be included in an amount of 0.1 wt % to 5 wt % relative to the total weight of the electrolyte.
[0125] Beneficial Effects
[0126] According to the present invention, there are provided an electrode-integrated separator having excellent adhesion durability without impairing ion conductivity between electrodes and a lithium ion secondary battery including the same. BRIEF DESCRIPTION OF THE DRAWINGS
[0127] Figure 1 is a cross-sectional view of an electrode-integrated separator for a lithium ion secondary battery according to an embodiment of the present invention.
[0128] Figures 2 to 6 Each of them is a cross-sectional view of a bonding portion pattern according to an embodiment of the present invention.
[0129] Figure 7 and Figure 8Each is a cross-sectional view showing a method for calculating an area ratio of a bonding part pattern according to an embodiment of the present invention.
[0130] Figures 9 to 12 2 are scanning electron microscope (SEM) images of a surface of a negative electrode part having a bonding part pattern formed thereon according to an embodiment of the present invention, respectively.
[0131] <Description of Reference Numerals>
[0132] 100: Electrode integrated separator for lithium secondary battery
[0133] 10: Electrode
[0134] 13: Electrode current collector
[0135] 15: Electrode active material layer
[0136] 20: Bonding pattern
[0137] 23, 25, 27: Adhesive unit
[0138] 30: Porous layer
[0139] A U : Unit area
[0140] A P : A U The area occupied by the bonding pattern DETAILED DESCRIPTION
[0141] Hereinafter, the action and effect of the present invention will be described in more detail with reference to specific embodiments of the present invention. However, this is presented as an embodiment to help understand the present invention. The following examples are not intended to limit the scope of the present invention in any way. It will be apparent to those skilled in the art that various changes and modifications can be made within the scope and technical spirit of the present invention.
[0142] Example 1
[0143] An aqueous active material slurry consisting of 95.6 wt % of an active material consisting of 90 wt % of a graphite active material in which artificial graphite and natural graphite are mixed at a ratio of 3:7 and 10 wt % of SiO2; 1 wt % of acetylene black as a conductive material; and 1.1 wt % of carboxymethyl cellulose (CMC) and 2.3 wt % of styrene-butadiene rubber (SBR) as a binder was prepared. The active material slurry was applied to one surface of a copper current collector at a thickness of 8 μm using a comma coater and dried. Then, it was rolled to form a negative electrode active material layer (thickness 44 μm) with a porosity of 24%.
[0144] The adhesive part (polyvinylidene fluoride) was printed with a gravure printing device. Figure 7 The form shown in is patterned on the negative electrode active material layer. At this time, the adhesive unit having a circular cross section is formed to a thickness of 1 μm so that the diameter of the cross section is 400 μm; the distance between the center parts of the adhesive unit is 900 μm; and the area ratio of the adhesive pattern to the total area of the negative electrode active material layer is 18%.
[0145] In order to prepare a porous layer composition, AlO(OH) as inorganic fine particles and dispersant DISPERBYK-111 (BYK) are mixed with N-methyl-2-pyrrolidone (NMP). Thus, an inorganic fine particle dispersion with a solid content of 42% is prepared. At this time, the particle size (D60) of the inorganic fine particles measured using a particle size analyzer is analyzed to be 400nm. 6 weight % of poly(vinylidene fluoride-co-hexafluoropropylene) and 5 weight % of the dispersant DISPERBYK-111 (BYK) are dissolved in NMP to prepare a binder solution. The inorganic fine particle dispersion and the binder solution are uniformly mixed using a homogenizer to obtain a slurry. The slurry is applied to a negative electrode active material layer having a bonding portion pattern formed thereon, followed by pressure lamination and drying at 130°C to obtain a layer having a bonding portion pattern formed thereon. Figure 1 A negative electrode plate having a porous layer having a thickness of 17 μm and a porosity of 50% was formed in the form shown in FIG. The composition of the porous layer was 90 parts by weight of inorganic fine particles and 10 parts by weight of a polymer binder.
[0146] The negative electrode plate was punched into a size of 31 cm×43 cm using a die punching machine to prepare a negative electrode integrated separator.
[0147] 94 wt% of LiNiCoMnO2 (Ni:Co:Mn=8:1:1) as a positive electrode active material, 3 wt% of conductive carbon black (Super P; IMERYS Graphite & Carbon) as a conductive material, and 3 wt% of polyvinylidene fluoride as a binder were mixed, and the mixture was added to NMP to prepare a uniformly dispersed slurry. The slurry was applied to one surface of the aluminum current collector, dried and rolled to prepare a positive electrode plate with a positive electrode active material layer stacked thereon. The positive electrode plate was punched into a size of 30 cm × 42 cm using a die punch to prepare a positive electrode portion.
[0148] The positive electrode active material layer of the positive electrode portion was disposed by being adjacent to the porous layer of the negative electrode integrated separator. Then, an electrode assembly was manufactured by pressurizing and laminating at 90°C.
[0149] The electrode assembly is stored in a pouch to form a small-sized battery, and an electrolyte is injected into the pouch to produce five lithium-ion secondary batteries.
[0150] At this time, as an electrolyte solution, a solution in which 1.0 M LiPF6 and 2 wt% of vinylene carbonate (VC) were dissolved in a nonaqueous organic solvent mixed with ethylene carbonate (EC) and ethyl methyl carbonate (EMC) at a volume ratio of 3:7 was used.
[0151] Example 2
[0152] An electrode integrated separator and a lithium ion secondary battery including the same are produced in the same manner as in Example 1, except that when forming the bonding portion pattern, the bonding portion unit having a circular cross-section is changed so that the diameter of the cross section is 400 μm; the distance between the center portions of the bonding portion units is 730 μm; and the area ratio of the bonding portion pattern to the total area of the negative electrode active material layer is 27%.
[0153] Example 3
[0154] An electrode integrated separator and a lithium ion secondary battery including the same are produced in the same manner as in Example 1, except that when forming the bonding portion pattern, the bonding portion unit having a circular cross-section is changed so that the diameter of the cross-section is 400 μm; the distance between the center portions of the bonding portion units is 630 μm; and the area ratio of the bonding portion pattern to the total area of the negative electrode active material layer is 37%.
[0155] Example 4
[0156] An electrode integrated separator and a lithium ion secondary battery including the same are produced in the same manner as in Example 1, except that when forming the bonding portion pattern, the bonding portion unit having a circular cross-section is changed so that the diameter of the cross-section is 400 μm; the distance between the center portions of the bonding portion units is 550 μm; and the area ratio of the bonding portion pattern to the total area of the negative electrode active material layer is 48%.
[0157] Comparative Example 1
[0158] An electrode-integrated separator and a lithium ion secondary battery including the same were produced in the same manner as in Example 1, except that the porous layer was formed directly on the negative electrode active material layer without forming the binding portion pattern.
[0159] Comparative Example 2
[0160] An electrode-integrated separator and a lithium ion secondary battery including the same were produced in the same manner as in Example 1, except that the binding portion was applied to one entire surface of the negative electrode active material layer to form the binding portion.
[0161] Experimental Example 1
[0162] The surfaces of the negative electrode portions having the bonding portion patterns formed thereon according to Examples 1 to 4 were observed using a scanning electron microscope, and the images are shown in FIG. Fig. 9 (Example 1), Fig.10 (Example 2), Fig.11 (Example 3) and Fig.12 (Example 4).
[0163] Experimental Example 2
[0164] Regarding the negative electrode integrated separators obtained in the examples and comparative examples, a 180-degree peel strength test was performed using a TA-XT2 Plus device from Stable MicroSystems according to the test method of ASTM D3330 (2018).
[0165] The sample (negative electrode integrated separator) was fixed vertically to the ground, and then the tape (3MScotch tape, width 18mm) was attached to the porous layer in a U shape. One end of the tape was hooked on the handle of the device, and the strength of the force applied to the handle was measured when it was peeled off 180 degrees while pulling in the vertical direction of the ground (measuring speed 300mm / min, measuring distance 5cm). The above tests were each carried out on five samples, and the average value of the 180 degree peeling force is shown in Table 1 below.
[0166] [Table 1]
[0167] 180 degree peeling force (gf / mm) Example 1 0.56 Example 2 0.57 Example 3 0.56 Example 4 0.58 Comparative Example 1 0.19 Comparative Example 2 0.61
[0168] In the 180-degree peel strength test, it was determined that in the negative electrode integrated separator of the embodiment, no peeling of the porous layer occurred, and the tape was peeled off smoothly. In contrast, it was determined that in the negative electrode integrated separator of Comparative Example 1, the porous layer was peeled off from the negative electrode portion, and stick-slip behavior occurred irregularly.
[0169] Experimental Example 3
[0170] The lithium ion secondary batteries obtained in the examples and comparative examples (5 samples each) were subjected to a CC-CV test at 25°C at 0.1C (reference capacity 4.5 mAh / cm 2 ) until the voltage reached 4.2 V, and the voltage was maintained in CV mode until it reached 0.05 C. Subsequently, a formation process was performed by discharging to 2.5 V at 0.1 C, and the discharge capacity (mAh) and ion conductivity (mS / cm) are shown in Table 2 below as average values of five samples.
[0171] During the formation process, the number of defective samples in which charging and discharging did not normally occur due to short circuits among the five samples each produced in Example and Comparative Example was determined and shown in Table 2 below.
[0172] [Table 2]
[0173]
[0174] Referring to Table 2, the lithium ion secondary battery of the example exhibited not only a high discharge capacity but also excellent assembly stability without defects due to a short circuit between the positive electrode portion and the negative electrode portion.
[0175] The lithium secondary battery of Comparative Example 1 exhibited a high level of discharge capacity, but no adhesive portion was applied, and thus the short-circuit rate of the electrode was high.
[0176] The lithium secondary battery of Comparative Example 2 exhibited the lowest levels of discharge capacity and ion conductivity because the entire negative electrode active material layer was incorporated with the binding portion.
[0177] Although the invention has been described in detail with reference to specific embodiments and illustrative drawings, the invention is not limited thereto and it will be apparent to those skilled in the art that various changes and modifications may be made within the spirit and scope of the disclosure as defined by the appended claims.
Claims
1. An electrode-integrated separator for a lithium-ion secondary battery, comprising: an electrode portion comprising an electrode active material layer stacked on an electrode current collector; forming a bonding portion pattern on the electrode active material layer; and A porous layer is closely bonded to the electrode active material layer through the bonding portion pattern and contains a polymer binder and inorganic fine particles dispersed in the polymer binder. 2 . The electrode-integrated separator for a lithium ion secondary battery according to claim 1 , wherein the bonding part pattern is formed at an area ratio of 15% to 50% based on the total area of the electrode active material layer. 3 . The electrode-integrated separator for a lithium ion secondary battery according to claim 1 , wherein the bonding portion pattern includes four or more bonding portion units. 4 . The electrode-integrated separator for a lithium ion secondary battery according to claim 3 , wherein the bonding portion units each independently have one or more cross-sectional shapes selected from a circle, an ellipse, a sector, a polygon, and a concave polygon. 5 . The electrode-integrated separator for a lithium ion secondary battery according to claim 3 , wherein the bonding section units are configured such that center portions of the respective bonding section units are arranged at equal intervals. 6 . The electrode-integrated separator for a lithium ion secondary battery according to claim 3 , wherein the adhesive section units are arranged at intervals such that a distance between center portions of the adhesive section units is 100 μm to 1500 μm. 7 . The electrode-integrated separator for a lithium ion secondary battery according to claim 3 , wherein a cross section of the adhesive portion unit has a major axis diameter of 20 μm to 5000 μm.
8. The electrode-integrated separator for a lithium-ion secondary battery according to claim 1, wherein the bonding portion pattern comprises one or more selected from the group consisting of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-trichloroethylene), poly(vinylidene fluoride-chlorotrifluoroethylene), polymethyl methacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, ethylene vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethylated polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, ethylene-propylene-diene terpolymer, sulfonated ethylene-propylene-diene terpolymer, styrene-butadiene rubber, fluororubber, and polyimide. 9 . The electrode-integrated separator for a lithium ion secondary battery according to claim 1 , wherein the porous layer comprises 10 to 99 wt % of the inorganic fine particles and 1 to 90 wt % of the polymer binder.
10. The electrode-integrated separator for a lithium ion secondary battery according to claim 1, wherein the polymer binder is one or more selected from the group consisting of polyvinylidene fluoride, poly(vinylidene fluoride-hexafluoropropylene), poly(vinylidene fluoride-trichloroethylene), poly(vinylidene fluoride-chlorotrifluoroethylene), polymethyl methacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, ethylene vinyl acetate copolymer, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethylated polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, ethylene-propylene-diene terpolymer, sulfonated ethylene-propylene-diene terpolymer, styrene-butadiene rubber, fluororubber, and polyimide.
11. The integrated electrode separator for a lithium-ion secondary battery according to claim 1, wherein the inorganic fine particles are one or more selected from the following: SrTiO3; SnO2; CeO2; MgO; NiO; CaO; ZnO; ZrO2; Y2O3; Al2O3; boehmite (AlO(OH)); Al(OH)3; TiO2; SiC; BaTiO3; Pb(Zr,Ti)O3; Pb 1-x La x Zr 1-y Ti y O3; Pb(Mg 1 / 3Nb 2 / 3 )O3 - PbTiO3; HfO2; Li3PO4; Li x Ti y (PO4)3 (0 < x < 2, 0 < y < 3); Li x Al y Ti z (PO4)3 (0 < x < 2, 0 < y < 1, 0 < z < 3); (LiAlTiP) x O y (0 < x < 4, 0 < y < 13); Li x La y TiO3 (0 < x < 2, 0 < y < 3); Li x Ge y P z S w (0 < x < 4, 0 < y < 1, 0 < z < 1, 0 < w < 5); Li x N y (0 < x < 4, 0 < y < 2); Li x Si y S z (0 < x < 3, 0 < y < 2, 0 < z < 4); and Li x P y S z (0 < x < 3, 0 < y < 3, 0 < z < 7). 12 . The electrode-integrated separator for a lithium ion secondary battery according to claim 1 , wherein the inorganic fine particles have a particle size of 0.001 μm to 10 μm. 13 . A lithium ion secondary battery comprising the electrode-integrated separator according to claim 1 .
